2003
DOI: 10.1007/s00429-002-0290-5
|View full text |Cite
|
Sign up to set email alerts
|

Embryos sired by males without accessory sex glands induce failure of uterine support: a study of VEGF, MMP and TGF expression in the golden hamster

Abstract: To account for reproductive failure induced by surgical deletion of paternal accessory sex glands in the golden hamster in vivo, we studied expression of vegf, FLT-1 (VEGF-R1), FLK-1 (VEGF-R2), MMP and TGF-beta in endometrium of the dam and sired embryos during 5-7 days post coitum by immunohistochemistry, in situ hybridisation, semiquantitative RT-PCR and enzyme-linked immunosorbent assay. Spatiotemporal pattern of vegf expression in the control animals was similar to that reported for intact animals by our g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…VEGF is expressed by unidentified stromal cells distributed similarly to macrophages adjacent to blood vessels and scattered throughout the endometrial stroma (Halder et al 2000;Shweiki et al 1993). VEGF mRNA expression in hamsters is reduced after mating with accessory-gland-deficient males (Chow et al 2003). …”
Section: Regulation Of Tissue Remodellingmentioning
confidence: 96%
“…VEGF is expressed by unidentified stromal cells distributed similarly to macrophages adjacent to blood vessels and scattered throughout the endometrial stroma (Halder et al 2000;Shweiki et al 1993). VEGF mRNA expression in hamsters is reduced after mating with accessory-gland-deficient males (Chow et al 2003). …”
Section: Regulation Of Tissue Remodellingmentioning
confidence: 96%
“…In particular, macrophage-secreted matrix metalloproteinases (MMPs) and tissue inhibitors of MMPs (TIMPs) coordinate their expression to contribute to this remodelling process (Robertson 2005 ). In rodents, MMPs and TIMPs are induced during the pre-implantation period (Das et al 1997 ;Feng et al 1998 ), with seminal plasma postulated to contribute to their induction as the absence of accessory gland fl uid at coitus in the hamster is associated with a reduction in MMP2 at the implantation site (Chow et al 2003 ).…”
Section: Endometrial Receptivity and Embryo Implantationmentioning
confidence: 99%
“…Macrophages are a potent source of vascular endothelial growth factor (VEGF) and other key angiogenic factors and vascular permeability agents (Yoshida et al 1997 ). The expression of these angiogenic factors is tightly regulated through the estrous cycle and early pregnancy (Ma et al 2001 ) with a reduction of VEGF mRNA expression in hamsters after coitus occurring when seminal fl uid signalling is perturbed by mating with accessory gland-defi cient males (Chow et al 2003 ). Evidence of a role for seminal fl uid in angiogenesis is also demonstrated by studies in the horse and pig which show an increase in uterine vasodilation and oedema in the days following coitus (O'Leary et al 2004 ;Bollwein et al 2003 ).…”
Section: Endometrial Receptivity and Embryo Implantationmentioning
confidence: 99%
“…Neutrophils have been identified as the key source of MMP-9, a collagen specific protease during the peri-implantation period [93], while macrophages are known to produce a range of MMPs. A comprehensive study by Chow et al [94] in the golden hamster showed that expression of molecules involved in ECM remodelling are controlled in a temporal and spatial manner and that seminal plasma is implicated in their regulation. VEGF, its receptors (VEGF-R1 and -R2) and MMP-2 expression in the uterus during the peri-implantation period were all upregulated by seminal plasma exposure at the time of conception.…”
Section: Tissue Remodelling and Seminal Plasmamentioning
confidence: 99%
“…Artificial insemination in sheep has also been shown to benefit from cervical seminal plasma exposure, resulting in an increased percentage of pregnant ewes [6]. Removal of the accessories sex glands in the golden hamster has shown significant reductions in the expression of angiogenic and embryotrophic factors within the peri-implantation endometrium [94]. Our own studies have demonstrated the susceptibility to the very early embryo in generating offspring with metabolic perturbations.…”
Section: Seminal Plasma and Assisted Reproductionmentioning
confidence: 99%